Synergy of Digital Technology Based on Miller’s Pyramid in Emergency Medical Education: A Literature Review - Reqgi First Trasia; Ni Made Anggira Dhira Vinaya; Ananda Najwa Khoirunnisa; Chalisa Nazwa Sarahah (Jurnal Ilmu Medis Indonesia, 2026)
Purpose: This study aims to examine the role of digital technology in emergency medical education as an effort to strengthen the Integrated Emergency Management System (SPGDT) and to enhance the clinical competence of healthcare professionals. Research Methodology: This study employs a literature review approach by analyzing various scientific articles obtained from electronic databases, including Google Scholar, PubMed, and ScienceDirect. The review focuses on the utilization of digital technologies such as educational videos, Realistic Immersive Learning Environments (RILE), and telemedicine in emergency medical education, as well as the implementation of digital technologies within SPGDT. Results: The findings indicate that the use of digital technology improves the effectiveness of the learning process, situational awareness, and decision-making skills in emergency situations. Furthermore, the digitalization of SPGDT through the use of videos, Artificial Intelligence (AI), Global Positioning Systems (GPS), and integrated systems contributes to faster response times and improved accuracy in emergency care delivery. Conclusions: The integration of digital technology in emergency medical education and emergency response systems has the potential to enhance clinical competence and support more effective and efficient healthcare services. Limitations: This study is inherently limited to the analysis of existing literature and lacks empirical data to validate the actual effectiveness of these digital technologies in real-world emergency settings. Contributions: This study provides a conceptual overview of the use of digital technology in emergency medical education and its contribution to strengthening SPGDT for healthcare professionals.